An International Review to Characterize the Role, Responsibilities, and Optimal Setting for Health Literacy Mediators - Madeline Spencer; Nenagh Kemp; Vaughan Cruickshank; Claire Otten; Rosie Nash (SAGE Publishing, 2021)
Health literacy is a critically important determinant of health and is influenced by access to supportive social networks and services. Global investment in education throughout the life course is required to support health literacy development. The aim of this review is to characterize the role, responsibilities, and the optimal setting for the emergent role of a Health Literacy Mediator (HLM). A scoping review of recent literature was conducted. The review revealed a lack of consensus on who should be teaching health literacy, and variability in confidence when teaching health literacy. Professionals reported facing barriers such as a lack of time, a lack of knowledge, and recognized that the health literacy needs of children worldwide are not being met. Further research into the role of HLM is required to determine who is best suited to this role and what their responsibilities will be to ensure consistent health literacy education.